The making of an expert engineer how to have a wonderful career creating a better world and spending lots of money belonging to other people - Trevelyan, James P. (Balkema Book, 2014)
This book sets out the principles of engineering practice, knowledge that has come to light through more than a decade of research by the author and his students studying engineers at work. Until now, this knowledge has been almost entirely unwritten, passed on invisibly from one generation of engineers to the next, what engineers refer to as "experience". This is a book for all engineers. It distils the knowledge of many experts in one volume. The book will help engineers enjoy a more satisfying and rewarding career and provide more valuable results for their employers and clients. The book focuses on issues often seen as "non-technical" in the world of engineering, yet it shows how these issues are thoroughly technical. Engineering firms traditionally have sought expert advice on these aspects from management schools, often regarding these aspects of engineering practice as something to do with psychology or organisational behaviour